A wideband equivalent circuit for stripline-fed cavity-backed slot radiating elements - Hernández-Escobar, Alberto; Abdo-Sánchez, María Elena; Camacho-Peñalosa, Carlos (IEEE, 2019)
An equivalent circuit for stripline-fed cavity-backed slot radiating elements is proposed. The proposed equivalent circuit consist of a transmission line model for the slot mode, a slot end-effect which includes the radiation, and a strip-slot transition model. The equivalent circuit is validated using both simulated and measurement results and good agreement is found over a bandwidth of 5 GHz in the 3.5 GHz band. Compared with other equivalent circuits from the literature, the proposed model is capable of providing physical insight and accurate results in a wide frequency band with the advantage of simplicity, a small number of elements and a clear behavior of its parameters.
Keywords: Circuitos electrónicos; Cavity-backed slot; Equivalent circuit; Stripline; Transmission line; Wideband